A constitucionalização do direito entre o público e o privado - Drey, Luís Carlos (Universidade do Vale do Rio do Sinos, 2007)
This work not only defends a direct entailing of the Basic Rights of the Public Being, but also of the particular ones. The subject, however, for to be very generic in the doctrine and jurisprudence, generates uncertainty in the contemporaneo right of as if it really gives the entailing and of that it forms, and if that is possible. Although not only let us defend the direct effectiveness of the basic rights in face of the State, but of the not public beings, the situations must be analyzed in concrete situations, a time that both the parts are possessing of indestructible rights (of the human being). Still the doctrine – as much of the comparative jurisprudence – as of the Brazilian right in this question is resistant. In the Brazilian right, this occurs for the lack of matureness and the daily pay-understanding of hermeneutics of the beddings of the Constitution of 1988 – in face of the great ditatoriais periods – that possess as anchor the Democratic State of Right and the Dignity of the Person Human being
Keywords: direito privado; direitos humanos; repersonalização; direitos fundamentais; Ciências Sociais Aplicadas